Engineering 3D copper foam current collectors: modification strategies and challenges toward stable lithium metal batteries - Dong-Run Yang; Qingsong Lai; Yu-Tong Long; Xu Shi; Yue Lu; Zhao-Meng Liu; Xuan-Wen Gao; Wen-Bin Luo (Science and Technology of Advanced Materials, 2025)
Lithium metal is a promising anode for high-energy batteries due to its high capacity and low density. However, issues like dendrite growth and volume expansion limit its practical use. To address these challenges, three-dimensional (3D) copper foam current collectors with porous architectures and superior electrochemical properties have emerged as a research focus. Three-dimensional copper foam current collectors have emerged as a strategic solution, leveraging their porous architecture to regulate lithium nucleation, enhance mechanical stability, and maintain electrochemical equilibrium. Despite their potential, current implementations confront four key constraints: excessively large pore sizes, uneven surface current distribution (leading to non-uniform lithium deposition, dendrite growth, and dead lithium formation), poor lithiophilicity, and weak oxidation resistance. These factors hinder the long-term suppression of lithium dendrites and degrade the oxidation resistance of copper nanostructures. This review systematically examines recent advancements in 3D copper foam engineering through three principal modification approaches: metallic/alloy coatings, surface functionalization, and structural optimization. The advantages, limitations, and critical issues of these approaches are analyzed. Furthermore, the importance of 3D copper foam current collectors in advancing lithium metal batteries is elucidated, highlighting current achievements, areas for improvement, and potential applications. Finally, recommendations and future prospects for further optimization of 3D copper foam current collectors are proposed to achieve commercially viable lithium metal batteries.